The international debate on generic medicines of biological origin - Germán Velásquez (South Centre, 2017)
The debate on generic medicines is not new. What makes it different today is that attacks levelled against biological products are couched in ever more "technical" and abstruse language that confuses even the World Health Organization (WHO). Innovative biological drugs, which have been introduced on the market in the past 20 to 30 years, make up, in terms of numbers, no more than 2 per cent of the WHO Model List of Essential Medicines but, in terms of cost, account for 15 per cent to 20 per cent of national drug expenditure. The high price of biological drugs stems mainly from two new factors: first, a change in the pharmaceutical industry's approach to price-setting and, secondly, the introduction of additional barriers to the entry of generics into the market. In any debate on the impossibility of producing "identical" drugs, it should be made clear that what is at stake is not identical products but therapeutic equivalents. What matters to the patient, after all, is whether or not the drug can prevent, cure or mitigate the effects of the illness.
Keywords: 300; Generika; Herkunftsbezeichnung; Gesundheitsrisiko; Arzneimittelrecht; Außenwirtschaftsrecht; Welt